An Analysis of Prenatal Yoga for Pregnant Women at Eka Sri Wahyuni Clinic - Pratiwi Syah Putri; Nurhaida br Kaban; Nopita Yanti Sitorus (PT Inovasi Pratama Internasional, 2022)
During pregnancy , mother pregnant will experience many very change that can causing and also causing a feeling of not comfortable especially when entering the second and third trimesters. Yoga practice being one method and effort To use overcome and also reduce the feeling of not comfortable as well as always physical get complained during pregnancy . Destination study this conducted To use knowing how much big influence of prenatal yoga on complaint physical as well as feeling not comfortable for mom second and third trimester of pregnancy . Research the use quasi -experimental method that is system one group pre test- post test design is taken from a number of sample respondent where use technique purposive sampling . Data analysis wear system dependent samples t test . this result will show average score complaint physique from mothers pregnant before doing prenatal yoga 7.63, meanwhile after do prenatal yoga, then got 4.80. The results of the dependent samples t test obtained a p value of 0.000. Conclusion from study the found that is prenatal yoga can be one reason decline complaint physique of pregnant women entering the second and third trimesters. It is hoped that prenatal yoga can conducted in a manner routine to Pregnant Women and can formed Prenatal Yoga class.